Adsorbation of Carbon Monoxide Gas With Activated Carbon From Rubber Fruit Shells - Sasmita, Aryo; Edward, Edward; Syahbana, Rudea Faddhisrah (Jurnal Teknologi, 2024)
Carbon Monoxide (CO) emitted by motorized vehicles can have a negative impact on human health. One way to absorb CO gas is with adsorption technology using activated carbon. Activated carbon has the potential to be used as an adsorbent. This research aims to study the efficiency of CO gas absorption in motorbike emissions using activated carbon from rubber fruit shells. Activated carbon was prepared by carbonization process at 500oC for 1 hour using 10% H3PO4 activator and sieving with a sieve size of 200 mesh. The operating conditions of the adsorption process that were varied were the length of the adsorbent, namely 3; 4; and 5 cm. The activated carbon product is then tested using proximate analysis. The results of proximate analysis show that activated carbon meets SNI 06-3730-1995 with a water content value of 7.6%; ash content 8.7%; volatile matter 8.2%; and fixed carbon 75.5%. The research results showed that the highest removal of CO gas emissions on motorbikes occurred at a contact time of 1 minute of 80.809% with a media thickness of 5 cm. The best adsorption capacity value occurred at a contact time of 1 minute, with an activated carbon media length of 3 cm, namely 158.635 mg/g.